Urban project is a strategic for formalizes spontaneous urbanization towards sustainable social development - Abbas, Shahad; Ebraheem , Mustafa (Al-Adab Journal, 2025)
The most important aspect of the 21st century is opening new frontiers in human settlements, the remarkable concentration of people in major global cities and increasing urbanization. According to United Nations projections, 75% of the Earth's population will reside in urban areas by 2050. While urbanization, the growth of cities, and globalization have accelerated social and economic development, from here came the research problem, which is that urban planners need to rethink the methods used for urban planning and design and the city they envision, and how to find solutions to the spontaneous urbanization process and move from it to urban design. Adaptable that harnesses the power of individual endeavour through sustainable urban projects. ‏The research discussed the concept of spontaneous urbanization's characteristics, reasons for its formation, challenges and opportunities. The concept of the urban project, its characteristics, and how to integrate it with sustainable development goals to design a sustainable urban project for spontaneous urbanization areas. The research assumed that spontaneity has a positive and negative side, and some researchers have addressed it with its positive meaning through international and Arab research. Benefiting from the positive characteristics and principles of spontaneous urbanization and how the urban project applies them to achieve sustainable social development. ‏Through global experiences, the research concluded that spontaneous urbanization can complement official systems by providing housing for those not covered by official urban plans. This aspect reflects the ability of people to organize themselves and meet their basic needs in the absence of government solutions, and also through the implementation of the project. Urban can be formalized and the phenomenon controlled, with governmental intervention framed through sustainable urban projects, aiming to create flexible, socially sustainable, adaptable and easy-to-understand environments. Strengthening local strengths and individual endeavours in projects that serve them.